Automated Synthesis and Initial Evaluation of (4′-Amino-5′, 8′-difluoro-1′H-spiro[piperidine-4, 2′-quinazolin]-1-yl)(4-[18F]fluorophenyl)methanone for PET/MR Imaging of Inducible Nitric Oxide Synthase. (8th July 2021) - Yeh, Skye Hsin-Hsien; Huang, Wen-Sheng; Chiu, Chuang-Hsin; Chen, Chuan-Lin; Chen, Hui-Ting; Chi, Dae Yoon; Ge, Zhengxing; Yu, Tsung-Hsun; Wang, Pao-Yeh; Kuo, Yu-Yeh; Hung, Chun-Tse; Li, Geng-Ying; et al.
Abstract : Background . Inducible nitric oxide synthase (iNOS) plays a crucial role in neuroinflammation, especially microglial activity, and may potentially represent a useful biomarker of neuroinflammation. In this study, we carefully defined a strategic plan to develop iNOS-targeted molecular PET imaging using (4 ′ -amino-5 ′, 8 ′ -difluoro-1 ′ H-spiro[piperidine-4, 2 ′ -quinazolin]-1-yl)(4-fluorophenyl)methanone ([ 18 F]FBAT) as a tracer in a mouse model of lipopolysaccharide- (LPS-) induced brain inflammation. Methods . An in vitro model, murine microglial BV2 cell line, was used to assess the uptake of [ 18 F]FBAT in response to iNOS induction at the cellular level. In vivo whole-body dynamic PET/MR imaging was acquired in LPS-treated (5 mg/kg) and control mice. Standard uptake value (SUV), total volume of distribution (V t ), and area under the curve (AUC) based on the [ 18 F]FBAT PET signals were determined. The expression of iNOS was confirmed by immunohistochemistry (IHC) of brain tissues. Results . At the end of synthesis, the yield of [ 18 F]FBAT was 2.2–3.1% (EOS), radiochemical purity was >99%, and molar radioactivity was 125–137 GBq/ μ mol. In vitro, [ 18 F]FBAT rapidly and progressively accumulated in murine microglial BV2 cells exposed to LPS; however, [ 18 F]FBAT accumulation was inhibited by aminoguanidine, a selective iNOS inhibitor. In vivo biodistribution studies of [ 18 F]FBAT showed a significant increase in the liver and kidney on LPS-treated mice. At 3 h postinjection of LPS, in vivo, the [ 18 F]FBAT accumulation ratios at 30 min post intravenous (i.v.) radiotracer injection for the whole brain, cortex, cerebellum, and brainstem were 2.16 ± 0.18, 1.53 ± 0.25, 1.41 ± 0.21, and 1.90 ± 0.12, respectively, compared to those of mice not injected with LPS. The mean area under the curve (AUC0-30min ), total volume of distribution (V t, mL/cm 3 ), and K i (influx rate) of [ 18 F]FBAT were 1.9 ± 0.21 - and 1.4 ± 0.22 -fold higher in the 3 h LPS group, respectively, than in the control group. In the pharmacokinetic two-compartment model, the whole brain K i of [ 18 F]FBAT was significantly higher in mice injected with LPS compared to the control group. Aminoguanidine, selective iNOS inhibitor, pretreatment significantly reduced the AUC0-30min and V t values in LPS-induced mice. Quantitative analysis of immunohistochemically stained brain sections confirmed iNOS was preferentially upregulated in the cerebellum and cortex of mice injected with LPS. Conclusion . An automated robotic method was established for radiosynthesis of [ 18 F]FBAT, and the preliminary in vitro and in vivo results demonstrated the feasibility of detecting iNOS activity/expression in LPS-treated neuroinflammation by noninvasive imaging with [ 18 F]FBAT PET/MRI.